2014
DOI: 10.1074/jbc.m113.531921
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidic Acid (PA)-preferring Phospholipase A1 Regulates Mitochondrial Dynamics

Abstract: Background: Phosphatidic acid (PA) is involved in membrane dynamics. Results: PA-preferring phospholipase A 1 (PA-PLA 1 ) affects mitochondrial morphology in an activity-dependent manner. Gene disruption of PA-PLA 1 in mice causes sperm malformation due to mitochondrial organization defects. Conclusion: PA-PLA 1 regulates mitochondrial dynamics. Significance: We demonstrate an in vivo function of PA-PLA 1 and suggest a possible mechanism of PA regulation of the mitochondrial membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
141
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(148 citation statements)
references
References 46 publications
4
141
0
1
Order By: Relevance
“…The cellular functions of PI (3,5)P2 might partially relate to ATP13A2, since loss of ATP13A2 results in neurodegeneration, an increased lysosomal pH and impaired autophagy. 2 We further show that ATP13A2 mediates protection against rotenone-induced mitochondrial stress requiring both catalytic activity of ATP13A2 and the lipids PA and PI (3,5)P2. This hints to a lipiddependent activation of ATP13A2 that is important for mitochondrial homeostasis and/or clearance 2 (Fig.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The cellular functions of PI (3,5)P2 might partially relate to ATP13A2, since loss of ATP13A2 results in neurodegeneration, an increased lysosomal pH and impaired autophagy. 2 We further show that ATP13A2 mediates protection against rotenone-induced mitochondrial stress requiring both catalytic activity of ATP13A2 and the lipids PA and PI (3,5)P2. This hints to a lipiddependent activation of ATP13A2 that is important for mitochondrial homeostasis and/or clearance 2 (Fig.…”
mentioning
confidence: 99%
“…1). In fact, we show that the signaling lipids phosphatidic acid (PA) and phosphatidylinositol (3,5)bisphosphate (PI(3,5)P2) interact with the N-terminal region. Biochemical evidence further indicated that ATP13A2 may reside in an inactive autophosphorylated state and that both lipids stimulate catalytic autophosphorylation, suggesting that the lipids unlock ATP13A2 activity.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Comprehensive analysis of phospholipids was conducted in essentially the same manner as described previously [28][29]. Briefly, total phospholipids were extracted from the plasma with the Bligh-Dyer method [30].…”
Section: Phospholipid Preparationmentioning
confidence: 99%